2020
DOI: 10.1038/s41598-020-71710-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tear film spatial instability for pediatric myopia under treatment

Abstract: In Taiwan, the prevalence of myopia in children between 6 and 18 years old is over 80%, and high myopia accounts for over 20%, which turned out to be in the leading place worldwide. Orthokeratology and low-dose atropine are proven treatments to reduce myopia progression, though the potential corneal disturbances remain an issue in young populations. The alteration of the tear film is widely discussed but there is no consensus to date, so we aim to investigate the tear film spatial instability in children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Ocular Surface Disease Index (OSDI), a subjective assessment, is one of the dry eye questionnaires that included items assessing patients’ health-related quality of life and were evaluated adequately for psychometric properties [ 5 ]. Measurement of tear film break-up time may provide a better indicator of the tear film stability to prevent evaporative tear fluid losses [ 6 , 7 , 8 ]. Compared to the Schirmer test, tear meniscus height (TMH) is a reliable, less invasive, higher reproducible, and cost-effective alternative to determine the tear volume [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular Surface Disease Index (OSDI), a subjective assessment, is one of the dry eye questionnaires that included items assessing patients’ health-related quality of life and were evaluated adequately for psychometric properties [ 5 ]. Measurement of tear film break-up time may provide a better indicator of the tear film stability to prevent evaporative tear fluid losses [ 6 , 7 , 8 ]. Compared to the Schirmer test, tear meniscus height (TMH) is a reliable, less invasive, higher reproducible, and cost-effective alternative to determine the tear volume [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (29) reported that TMH was significantly increased at 1 and 3 months compared with the pre-wearing level but did not affect the meibomian gland function. In the study reported by Cho, there was no significant difference in TMH and TBUT between children with different myopia treatment methods and normal children (35). Xie et al (30) showed that the use of OK lenses did not affect basic tear secretion and ocular surface inflammation in myopic children.…”
Section: Discussionmentioning
confidence: 89%
“…Of course, there are certain disadvantages to orthokeratology since it must make direct contact with the cornea, which can change the ocular surface and cause the stability of the tear lm to shift in a distinctive way [22] . As the most anterior refractive surface of the eye, the tear lm is crucial to achieving high optical quality of the ocular surface.…”
Section: Discussionmentioning
confidence: 99%